Second language learning and the creation of a sense of belonging : experiences of international PhD students in Finland - Weingärtner, Katharina Bettina (2023)
Embedded in the context of internationalization of Higher Education, the focus of this study is on the reciprocal relationship between the Finnish language learning process of international PhD students and the development of a sense of belonging. Based in the paradigmatic framework of Social Constructionism this study follows a qualitative approach. Through semi-structured interviews I was able to collect data from nine international PhD students. Grounded in the theoretical concepts of belonging and Second Language Socialization, I analyzed the data through a reflexive thematic approach to address the following research questions: How do the experiences of international PhD students in learning Finnish perceivably influence their sense of belonging in Finland? How do the experiences of international PhD students of their social interactions and relations within their environment perceivably influence their sense of belonging in Finland? The findings of this study, which were structured around four main themes – perceptions of Finland and how they perceivably influence belonging, intentions of learning Finnish and the developments, language as a form of inclusion versus language as a form of exclusion, and living in a(n English) bubble – illuminate the multifaceted nature of international PhD students’ experiences in creating a sense of belonging in Finland and the potential influence of their language learning journey on this sense. The study contributes to a deeper understanding of these experiences and can offer valuable insights for the students themselves as well as for Higher Education Institutions seeking to enhance language learning opportunities for international PhD students.